2019
DOI: 10.1016/j.dib.2019.104590
|View full text |Cite
|
Sign up to set email alerts
|

Dataset on the hygrothermal performance of a date palm concrete wall

Abstract: The present data article is concerned with the hygrothermal performance at the wall scale of a new bio-based building material including date palm fibres. A specific test setup allowed to measure temperature and relative humidity (RH) profiles at three different depths of the bio-based wall subjected to outdoor boundary conditions. Besides, a partial differential equations resolution software was then used to solve two mathematical models (i.e., Kunzel and Mendes models) describing heat and moisture transfer i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…A numerical comparison was made between DPC and a conventional building material in terms of thermal insulation and moisture buffering capacity. The findings revealed that the new bio-based wall would help minimize temperature fluctuations and increase building hydrothermal comfort [80,81].…”
Section: Date Palm Woodmentioning
confidence: 99%
“…A numerical comparison was made between DPC and a conventional building material in terms of thermal insulation and moisture buffering capacity. The findings revealed that the new bio-based wall would help minimize temperature fluctuations and increase building hydrothermal comfort [80,81].…”
Section: Date Palm Woodmentioning
confidence: 99%
“…A numerical comparison was made between DPC and a conventional building material in terms of thermal insulation and moisture buffering capacity. The findings revealed that the new bio-based wall would help minimize temperature fluctua-tions and increase building hydrothermal comfort [80,81]. F. Alfa fibres The alfa "esparto grass" or Stippa Tenacissima (Fig.…”
Section: E Date Palm Woodmentioning
confidence: 99%
“…Details of the used scenarios are displayed in Table 2. Additional details regarding the experimental setup and the protocols can be found in [27,28].…”
Section: Experimental Test At the Wall Scalementioning
confidence: 99%